TiF 4 varnish protects the retention of brackets to enamel after in vitro mild erosive challenge (Journal of Applied Oral Science, 2022)
The effect of fluoride agents on the retention of orthodontic brackets to enamel under erosive challenge is little investigated. Objective: The aim of this study was to evaluate the effect of titanium tetrafluoride (TiF4) and sodium fluoride (NaF) agents on the shear bond strength of brackets to enamel and on the enamel microhardness around brackets under erosive challenge. Methods: Brackets were bonded to bovine incisors. Five groups were formed according to fluoride application (n=10): TiF4 varnish, TiF4 solution, NaF varnish, NaF solution and control (without application). The specimens were submitted to erosive challenge (90 s cola drink/2h artificial saliva, 4x per day for 7 days). Solutions were applied before each erosive cycle and varnishes were applied once. Vickers Microhardness (VHN) was obtained before and after all cycles of erosion and the percentage of microhardness loss was calculated. Shear bond strength, adhesive remnant index and polarized light microscopy were conducted after erosion. The data were analyzed by ANOVA, Tukey, Kruskal-Wallis and Mann-Whitney U tests (α=0.05). Results: The %VHN had no statistically significant differences among the experimental groups. However, considering the comparisons of all groups with the control group, TiF4 varnish showed the highest protection from enamel demineralization (effect size of 2.94, while the effect size for the other groups was >2.4). The TiF4 varnish group had significantly higher shear bond strength compared to other groups. There was no difference among groups for adhesive remnant index. Polarized light microscopy showed higher demineralization depth for the control group. Conclusions: Application of NaF and TiF4 agents during mild erosive challenge minimized the enamel mineral loss around brackets, however only the experimental TiF4 varnish was able to prevent the reduction of shear bond strength of brackets to enamel.